Glucocorticoid Metabolism in Obesity and Following Weight Loss - Akalestou, Elina; Genser, Laurent; Rutter, Guy A. (Frontiers in Endocrinology, 2020)
Glucocorticoids are steroid hormones produced by the adrenal cortex and are essential for the maintenance of various metabolic and homeostatic functions. Their function is regulated at the tissue level by 11β-hydroxysteroid dehydrogenases and they signal through the glucocorticoid receptor, a ligand-dependent transcription factor. Clinical observations have linked excess glucocorticoid levels with profound metabolic disturbances of intermediate metabolism resulting in abdominal obesity, insulin resistance and dyslipidaemia. In this review, we discuss the physiological mechanisms of glucocorticoid secretion, regulation and function, and survey the metabolic consequences of excess glucocorticoid action resulting from elevated release and activation or up-regulated signalling. Finally, we summarise the reported impact of weight loss by diet, exercise or bariatric surgery on circulating and tissue-specific glucocorticoid levels and examine the therapeutic possibility of reversing glucocorticoid-associated metabolic disorders.